Evaluation of Liver, Kidney, and Spleen Elasticity in Healthy Newborns and Infants Using Shear Wave Elastography. (18th April 2017) - Palabiyik, Figen Bakirtas; Inci, Ercan; Turkay, Rustu; Bas, Derya
Abstract : Objectives: Elasticity measurements of tissues can be valuable in the diagnosis and management of various diseases. The aim of this study was to determine the elasticity values for normal liver, kidney, and spleen of healthy newborns and infants using shear wave elastography (SWE) imaging. Methods: A total of 50 healthy term newborns and infants (19 girls and 31 boys; mean age 20.1 days, range 1 to 70 days) were examined by an experienced pediatric radiologist using SWE. None of them had any liver, kidney or spleen disease, or any other systemic disease that could affect these organs secondarily. All newborns and infants had a normal abdominal ultrasound scan. Results: Age, sex, weight, height, and body mass index had no significant effects on shear wave velocity (SWV) values of liver and spleen. The SWV values of both kidneys decreased with age, weight, height, and body mass index. The mean SWV values were 1.70 m/s (range: 1.23–2.43 m/s) for the liver, 1.69 m/s (range: 0.8–2.40 m/s) for the right kidney, 1.70 m/s (range: 0.9–2.49 m/s) for the left kidney, and 2.03 m/s (range: 1.28–2.48 m/s) for the spleen. Conclusions: Shear wave elastography can be used to measure liver, kidney, and spleen elasticity in newborns and infants. The standard values for abdominal organs allow differentiation of healthy versus pathological tissue. We measured the normal values of SWE in healthy newborns and infants as reference data.